PSYCHOLOGICAL FEATURES OF THE DEVELOPMENT OF PROFESSIONAL SELF-DETERMINATION OF STUDENTS OF SENIOR CLASSES OF SECONDARY EDUCATIONAL INSTITUTIONS (Psychology Travelogs, 2024)
The article defines the psychological features of the development of professional self-determination of high school students, which involves taking into account the features of the development of the value-meaning nature of the individual, methods and tools of interaction between the environment, the personality and the world of professions. Approaches to determining the content of the concept of «self-determination» are revealed, the content of the concept of «professional self-determination of an individual» is characterized as a long process through which a person understands his professional interests, abilities, values, and also sets career goals for himself and chooses the direction of professional development.The key aspects of psychological readiness for choosing a profession are analyzed, such as: self-awareness, high self-esteem, ability to make responsible decisions, motivation, critical thinking, stress resistance and readiness for continuous improvement. The factors affecting the individual's choice of future professional activity are determined.The periods of choosing a future professional activity are clarified, namely: self-discovery, determination of landmarks, choice of a specific profession, adaptation to training and professional environment, as well as career development. It is noted that each stage is important for future success, therefore support and help in these periods is important to ensure the correct and conscious choice of profession.The components of a professional plan as a strategic document that reflects the long-term and short-term goals of an individual in professional life, as well as ways to achieve them, are revealed.It is emphasized that soft skills play an important role in the formation of interest in choosing a profession among high school students, as they contribute not only to professional development, but also help students to realize their priorities, needs and abilities, which are key to a conscious career choice.The main forms that contribute to the professional self-determination of high school students are identified: career guidance consultations, career guidance events (career fairs, career days), project activities, psychological testing, excursions to enterprises and educational institutions, role-playing games and trainings, exhibitions and conferences, volunteering and community activities.It is noted that psychologists and teachers use various methods to help students determine their profession, in particular: tests for professional orientation, self-analysis and reflection, methods: «Map of career opportunities», «Forecasting the future», «Family consultation», «Professional adventures», career counseling, analysis of successful examples and role models.Techniques that contribute to effective professional self-determination are defined: compiling a personal profile, meeting with representatives of professions, role-playing games, collecting information about professions, testing for professional orientation, developing a career project, engaging mentors, practical experience through internships, visiting exhibitions, conferences, master classes for immersion in the professional environment, consultations with parents and relatives.The features of the psychologist's work on the formation of professional self-determination of high school students are revealed, among which the following can be named: an individual approach to each student, professional orientation through testing and diagnostics, interviews and counseling, work with motivation and overcoming stereotypes, analysis of life goals and values, development of professional skills through practical activities, group classes and trainings, preparation for choosing and analysis of possible development paths, support in the decision-making process.The role of parents in the formation of professional self-determination of high school students is determined, which consists in helping the child understand himself, his interests and capabilities, as well as creating an atmosphere that allows making an informed and independent decision.
Keywords: self-determination; professional orientation; professional self-determination of the individual; professional interests; soft skills